1998
DOI: 10.1126/science.282.5390.938
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Hepatitis C Virus to CD81

Abstract: Chronic hepatitis C virus (HCV) infection occurs in about 3 percent of the world's population and is a major cause of liver disease. HCV infection is also associated with cryoglobulinemia, a B lymphocyte proliferative disorder. Virus tropism is controversial, and the mechanisms of cell entry remain unknown. The HCV envelope protein E2 binds human CD81, a tetraspanin expressed on various cell types including hepatocytes and B lymphocytes. Binding of E2 was mapped to the major extracellular loop of CD81. Recombi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
1,484
3
24

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,881 publications
(1,549 citation statements)
references
References 18 publications
27
1,484
3
24
Order By: Relevance
“…Finally, Niemann-Pick C1-like 1 (NPC1L1) has been shown to support HCV entry, but its exact role is, as yet, unclear. 6 Cell-surface factors essential for HCV entry, but not directly involved in lipid trafficking, include the tetraspanin, CD81, 7 and the tight-junction components, claudin-1 8 and occludin. 9 SR-BI is a 509-amino-acid protein with two transmembrane domains and a single large extracellular loop that is highly expressed in the liver and in tissues producing steroid hormones.…”
mentioning
confidence: 99%
“…Finally, Niemann-Pick C1-like 1 (NPC1L1) has been shown to support HCV entry, but its exact role is, as yet, unclear. 6 Cell-surface factors essential for HCV entry, but not directly involved in lipid trafficking, include the tetraspanin, CD81, 7 and the tight-junction components, claudin-1 8 and occludin. 9 SR-BI is a 509-amino-acid protein with two transmembrane domains and a single large extracellular loop that is highly expressed in the liver and in tissues producing steroid hormones.…”
mentioning
confidence: 99%
“…In addition, the expression level of turtle CD9 gene in liver was the highest among examined tissues, which was differ from other known CD9s (rat and fish CD9). Although other tetraspanin family members such as CD81 were expressed strongly in liver [31][32][33], Warskulat et al found that most of CD9 expression was only restricted to Kupffer cells (the macrophages in hepatic sinuoid) [34]. Thus, our results are of great interest.…”
Section: Discussionmentioning
confidence: 55%
“…The binding activity between 18 positive clones and hCD81-expressing MOLT-4 cells could be inhibited by the anti-hCD81 MAb. It has been proved that the MAb used in this study can block the site of HCV E2 binding to hCD81 [2], thus indicating these 18 clones should be of the same determinant as HCV E2. Although the DNA sequences of these 18 clones were not identical, 12 out of the phage clones displayed the amino acid motif SPQYWTGPA.…”
Section: The Motif-containing Phages Specific To Hcd81 On Cell Membranementioning
confidence: 66%
“…Although the virus was identified more than a decade ago, some events in cell entry, replication and morphogenesis have not been well understood. It has been demonstrated that HCV envelope glycoprotein 2 (E2) could bind to host cells by interacting with the CD81 molecule [2]. CD81 is a membrane protein of 26 000 KD, and with four transmembrane (TM) and two extracellular (EC) domains, it belongs to the tetraspanin superfamily [3].…”
Section: Introductionmentioning
confidence: 99%